2006
DOI: 10.1007/s00384-006-0231-5
|View full text |Cite
|
Sign up to set email alerts
|

Curative in situ ablation of colorectal liver metastases—experimental and clinical implementation

Abstract: On the basis of experimental data, the aim of complete local tumor control (R0 ablation) can only be obtained if additional energy is applied after reaching the tumor-adapted maximal coagulation volume. Analogous to the oncological safety margin in surgical resection, we defined this decisive energy difference as the "energy safety margin" for in situ ablation. The energy safety margin is the energy that must be additionally applied after reaching the plateau in the energy/volume curve to achieve complete tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
1
0
2
Order By: Relevance
“…Furthermore, the volumes of treated metastases seemed to be a prognostic factor for long-term and progression-free survival as well. For example, Isbert et al 30 found significantly less local recurrences after in situ ablation for small-sized tumors of 3 cm in diameter or smaller. Solbiati et al 29 published comparable results using radiofrequency ablation: the local recurrence rate was between 21.6% for metastases up to a diameter of 2.5 cm and 68.4% for lesions 4.1 cm or larger.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, the volumes of treated metastases seemed to be a prognostic factor for long-term and progression-free survival as well. For example, Isbert et al 30 found significantly less local recurrences after in situ ablation for small-sized tumors of 3 cm in diameter or smaller. Solbiati et al 29 published comparable results using radiofrequency ablation: the local recurrence rate was between 21.6% for metastases up to a diameter of 2.5 cm and 68.4% for lesions 4.1 cm or larger.…”
Section: Discussionmentioning
confidence: 97%
“…! [2,3,37,39,47,53,92,105,125,141] Allgemeines Evidenzlage der In-situ-Ablation " Niedrige Morbidität / Mortalität " 5-Jahres-Überleben in (ungünstig) selektionierten Studien für nicht-resektable Metastasen vergleichbar zur alleinigen chirurgischen Resektion (Evidenz-Level III) " Vergleichsdaten LITT / RFA (Laserinduzierte Interstitielle Thermotherapie / Radiofrequenzablation) fehlen " Fehlende Angaben über 5-Jahres-Überleben nach Ablation resektabler kolorektaler Lebermetastasen " Der Effekt der RFA auf das Lanzeitüberleben verglichen mit einer alleinigen Chemotherapie ist nicht geklärt. " In den vorliegenden Studien über die Ergebnisse der ablativen Verfahren sind die Patientenkollektive unzureichend charakterisiert (fehlende Prognose-Scores).…”
Section: Lokal Destruierende Maßnahmenunclassified
“…Während bei chirurgischen Therapien die R0-Resektion histologisch überprüft werden kann, ist dies bei den nichtchirurgischen Interventionen nicht möglich [12]. Deshalb wird ein Sicherheitsabstand von 1 cm um den abladierten Tumor propagiert [13]. Bei hyperthermen Methoden (Radiofrequenzablation (RFA), LITT, perkutane Mikrowellen-Koagulationstherapie (PMCT)) werden Ablationstemperaturen von 60-100 °C angestrebt, bei denen irreversible Proteindenaturierungen und Koagulationsnekrosen auftreten.…”
Section: Ablative Verfahrenunclassified